Computational Cost Reduction for Real-Time Schedulability Tests Algorithms - Urriza, José Manuel (2015)
This paper focuses on reducing the computational cost of iterative algorithms used to evaluate the schedulability of Real-Time Systems. These algorithms calculate the worst case response time of each task. Through simulations it is found that the proposed new algorithm produces a significant reduction in the average temporal cost, reaching in some cases a reduction of O(n2) to O(n.log(n)), with respect to classical response time evaluation algorithms.